Influence of uvrD3, uvrE502, and recL152 mutations on the phenotypes of Escherichia coli K-12 dam mutants. - Marinus, M G (1980)
The recF143 allele did not alter the phenotypes of dam mutants of Escherichia coli. The uvrD3, uvrE502, and recL152 mutations did alter some of the phenotypes of dam bacteria. It was concluded that the uvrD, uvrE, and recL gene products are involved in the same deoxyribonucleic acid repair pathway as the dam gene product.